English Interaction in EFL Context by Using The Virtual Platform at The Coastal Area School - Haris Danial; Rahmatan Idul; Zulva Rosari Usman (Ideas Publishing, 2021)
The main purpose of this research is oriented to the description of communication strategies or interactions that occur in learning English speaking skills through a virtual platform. Specifically, the objectives of this research can be: 1) Describe the teacher's communication strategy in learning English speaking skills through virtual platforms in coastal schools; 2) Describe the interaction of students in learning English speaking skills through a virtual platform. The subjects of this study were teachers and students in coastal schools, in this case SMA Negeri 1 Bone Pantai. The instruments used in this study were field observations and open interviews. The finding of this research oriented to teacher’s intercation at platform meeting by considering some emotional feature such approving feeling, encouraging, receiving students’ ideas, asking questions, lecturing, and confering direction. The students’ interaction to the teacher have been implemented by students’ questions and giving inititation. They shared each other the first before asking more to the teacher, and even for the teacher, they just asked difficult words or expression. Tujuan utama penelitian ini berorientasi pada gambaran strategi komunikasi atau interaksi yang terjadi dalam pembelajaran keterampilan berbicara bahasa Inggris melalui platform virtual. Secara spesifik, tujuan penelitian ini dapat berupa: 1) Mendeskripsikan strategi komunikasi guru dalam pembelajaran keterampilan berbicara bahasa Inggris melalui platform virtual di sekolah pesisir; 2) Mendeskripsikan interaksi siswa dalam pembelajaran keterampilan berbicara bahasa Inggris melalui platform virtual. Subyek penelitian ini adalah guru dan siswa di sekolah pesisir, dalam hal ini SMA Negeri 1 Bone Pantai. Instrumen yang digunakan dalam penelitian ini adalah observasi lapangan dan wawancara terbuka. Temuan penelitian ini berorientasi pada interaksi guru pada pertemuan platform dengan mempertimbangkan beberapa fitur emosional seperti menerima perasaan, memuji atau mendorong, menerima atau menggunakan ide siswa, mengajukan pertanyaan, ceramah, dan memberi arahan. Interaksi siswa dengan guru telah dilaksanakan dengan pertanyaan siswa dan pemberian inisiasi. Berkaitan dengan pelajaran bahasa Inggris, siswa berinteraksi dengan temannya dengan membicarakan kegiatan yang ditanyakan guru, mendiskusikan pertanyaan guru, dan menanyakan kata atau ungkapan yang sulit.